Performance analysis of rooftop greenery systems in Australian subtropical climate - M. Anwar; M. G. Rasul; M. M. K. Khan (Energy Reports, 2020)
This paper presents the performance analysis of an extensive rooftop greenery system (green roof) in buildings in the Australian Subtropical climate, both experimentally and computationally. The impact of green roof systems on building thermal performance, energy consumption and energy savings are examined and compared with a non-green roof system in both experimentally and using computer simulation software called DesignBuilder (DB). For the experimental study, a shipping container with a green roof was converted into an office building. For comparison purposes, another shipping container of the same dimensions without a green roof layer was constructed and decorated in an identical way to the green roof container. Two computational models, one for green roof and other for non-green roof were developed. A 4~°C temperature difference between the green roof and non-green roof containers was observed on a typical summer day. For the green roof, the maximum variation between the simulated and measured data was found to be 5% for temperature, 7.5% for humidity and 9.4% for energy consumption. The study found that an extensive green roof on a building in the Central Queensland sub-tropical climate (Australia) can achieve energy savings of 13.65% (simulated) and 11.70% (measured) compared to a non-green roof.
Keywords: 330; Design builder; Energy consumption; Green roof; Subtropical; Thermal